Fundamentals of rigid body dynamics - Ahmad Fakri Shaari; Anwar P. P. Abdul Majeed (Penerbit Universiti Malaysia Pahang, 2014)
The module is written in such a way that the readers are furnished with elaborated first principle derivations as well as detailed worked examples